Pretreatment and gaseous radiocarbon dating of 40-100 mg archaeological bone - Fewlass, Helen; Kromer, Bernd (Scientific reports, 2019)
Radiocarbon dating archaeological bone typically requires 300-1000 mg material using standard protocols. We report the results of reducing sample size at both the pretreatment and 14C measurement stages for eight archaeological bones spanning the radiocarbon timescale at different levels of preservation. We adapted our standard collagen extraction protocol specifically for <100 mg bone material. Collagen was extracted at least twice (from 37-100 mg material) from each bone. Collagen aliquots containing <100 μg carbon were measured in replicate using the gas ion source of the AixMICADAS. The effect of sample size reduction in the EA-GIS-AMS system was explored by measuring 14C of collagen containing either ca. 30 μg carbon or ca. 90 μg carbon. The gas dates were compared to standard-sized graphite dates extracted from large amounts (500-700 mg) of bone material pretreated with our standard protocol. The results reported here demonstrate that we are able to reproduce accurate radiocarbon dates from <100 mg archaeological bone material back to 40,000 BP.
Gesehen am 12.06.2019